A 'jump-to-coalescence' mechanism during nanoparticle growth revealed by in situ aberration-corrected transmission electron microscopy observations. (12th April 2016) - Neng, Wan; Shuang-ying, Lei; Jun, Xu; Martini, Matteo
Abstract: In this work, we used in situ aberration-corrected transmission electron microscopy (AC-TEM) to observe the coalescence of gold nanoparticles. We observed a critical edge-to-edge distance d e c ∼ 0.5 nm below which the two particles will coalesce rapidly (jump-to-coalescence). A model based on the single-atom-triggered rapid particle contraction was proposed and verified by first-principles calculations, in which evident energy decrease was detected when adding a gold atom between two gold nanoparticles. Our ex situ TEM study of sputtering-deposited gold nanoparticles on different substrates with varied time also supports the jump-to-contact mechanism. This observation afforded physical insight into the fundamental growth mechanism during dynamic particle coalescence processes.